2017
DOI: 10.18632/oncotarget.19278
|View full text |Cite
|
Sign up to set email alerts
|

miR-19b promotes breast cancer metastasis through targeting MYLIP and its related cell adhesion molecules

Abstract: miR-19b is a key molecule for cancer development, however its crucial roles in breast cancer metastasis are rarely studied right now. In this study, using several bioinformatics databases to predict the downstream targets for miR-19b, we verified that a novel target gene, myosin regulatory light chain interacting protein (MYLIP), could be directly down-regulated by miR-19b through its 3′-UTR region. MYLIP belongs to the cytoskeletal protein clusters and is involved in the regulation of cell movement and migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“… 29 In breast cancer, the expression of miR-19b has also been investigated and was demonstrated to be elevated in tumor tissues compared with the normal controls. 30 Similarly, the results of our research revealed that miR-19b expression, measured by qRT-PCR, was markedly higher in breast cancer tissues than in the matched normal tissues. The expression results in breast cancer cells were inconsistent with the tissues, which also showed increased miR-19b expression levels in cancer cell lines compared with the normal cells.…”
Section: Discussionsupporting
confidence: 73%
“… 29 In breast cancer, the expression of miR-19b has also been investigated and was demonstrated to be elevated in tumor tissues compared with the normal controls. 30 Similarly, the results of our research revealed that miR-19b expression, measured by qRT-PCR, was markedly higher in breast cancer tissues than in the matched normal tissues. The expression results in breast cancer cells were inconsistent with the tissues, which also showed increased miR-19b expression levels in cancer cell lines compared with the normal cells.…”
Section: Discussionsupporting
confidence: 73%
“…Myosin-regulated light chain interacting protein (MYLIP), also known as ubiquitin-protein ligase, regulates the post-transcriptional diversity of low-density lipoprotein (LDL) receptors. Studies have confirmed that MYLIP inhibits the metastasis and progression of breast cancer [35]. Our study indicated that MYLIP was a tumor suppressor during the progression of LUAD, and hypoxia promoted DNA methylation of MYLIP.…”
Section: Discussionsupporting
confidence: 68%
“…Compared with the untreated cells, miR-19b was significantly downregulated in SGC-7901 cells following matrine treatment. Another study reported that miR-19b promoted breast cancer metastasis by targeting myosin regulatory light chain interacting protein and associated cell adhesion molecules (19). Additionally, it has been reported that miR-19b-3p may promote colon cancer proliferation and oxaliplatin-based chemoresistance by targeting SMAD4 (20).…”
Section: Introductionmentioning
confidence: 99%